Back pain and its association with the practice of body mechanics among healthcare providers in Hospital Universiti Sains Malaysia - Harun, Nurul Afiqah (Universiti Sains Malaysia, 2023)
Back pain is widely prevalent in the general population especially among healthcare professionals due to the increased exposure to physical demands of their work routine. This study aims to determine the incidence of back pain symptoms, the level of practice of body mechanics, the association between the practice of body mechanics and back pain symptoms, and the related factors that contributed to back pain symptoms among healthcare providers in Hospital USM. A cross-sectional survey was carried out on 218 respondents that were recruited using convenience sampling in a 10 random selected departments. The data collection period was from October 2022 until June 2023. A set of self- administered questionnaire via google form was used to collect the data. The data was analyzed using software SPSS (26.0). The result shows that 177 healthcare providers out of 218 experienced back pain symptoms in the preceding 12 months. The healthcare providers that worked at Hospital USM had good level of body mechanic practice. A significant association (p=0.002) was indicated between back pain symptoms and the level of body mechanic practices among healthcare providers in Hospital USM.